The Appropriateness On Consumption Of Es Krim Pot According To The Storage Places And Different Variant Of Topping Sold Around Muhammadiyah University Of Surakarta Campus With Mpn Method - Satria Mukti, Taufiq (Universitas Muhammadiyah Surakarta, 2016)
Ice Cream is dairy milk product which is a bit solid and tasty because of the various ingredients mixed in the making process. The presentation of Ice Cream itself is more creative and innovative, one of them is "Es Krim Pot". This research is aimed to find out about the appropriateness of es krim pot which is sold around UMS Campus using MPN method. The testing held in Microbiology Laboratory of Biology, School of Teacher Training and Education-UMS with two process, they are, Presumptive Test with LB and Confirmed Test with BGLB. The appropriateness on consumption of es krim pot will be found by comparing the amount of MPN fecal coliform bacteria with the provision by BPOM RI Number HK 00.06.1.52.401.2009 that the maximum limit is 3 MPN/ml. Samples used are from 3 different seller (P1,P2, and P3) with 2 different sampling time, they are 11.00 (W1) and 15.00 (W2). The result obtained consecutively, are P1W1 = 0,42 MPN/ml; P1W2 = 11 MPN/ml; P2W1 = 0,44 MPN/ml; P2W2 = 2,9 MPN/ml; P3W1 = 0,03 MPN/ml; P3W2 = 2,1 MPN/ml. From the result, it can be concluded that every seller are appropriate on consuming because according to the provision by BPOM on 2009 the amount of MPN fecal coliform are under 3 MPN/ml except on P1W2, in the amount of 11 MPN/ml, stated as inappropriate.